2016
DOI: 10.1007/s10815-016-0760-y
|View full text |Cite
|
Sign up to set email alerts
|

The clinical application of preimplantation genetic diagnosis for the patient affected by congenital contractural arachnodactyly and spinal and bulbar muscular atrophy

Abstract: Purpose To investigate the usefulness of preimplantation genetic diagnosis (PGD) for the patient affected by congenital contractural arachnodactyly (CCA) and spinal and bulbar muscular atrophy (SBMA). Methods Multiple displacement amplification (MDA) was performed for whole genome amplification (WGA) of biopsied trophectoderm (TE) cells. Direct mutation detection by sequencing and next-generation sequencing (NGS)-based single nucleotide polymorphism (SNP) haplotyping were used for CCA diagnosis. Direct sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Moreover, another advantage of haplotyping is the ability to identify meiotic recombination, which can impair the accuracy of PGD (Altarescu et al 2008). We previously diagnosed congenital contractural arachnodactyly via NGS-based SNP haplotyping and observed homologous recombination of maternal origin, but this effect did not impair the accuracy of PGD due to the more informative SNPs used in this case (Chen et al 2016). Therefore, haplotyping presents a number of advantages over the direct mutation detection by PCR, including the detection of ADO, chromosomal monosomy and recombination, to ensure the accuracy of clinical diagnosis.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, another advantage of haplotyping is the ability to identify meiotic recombination, which can impair the accuracy of PGD (Altarescu et al 2008). We previously diagnosed congenital contractural arachnodactyly via NGS-based SNP haplotyping and observed homologous recombination of maternal origin, but this effect did not impair the accuracy of PGD due to the more informative SNPs used in this case (Chen et al 2016). Therefore, haplotyping presents a number of advantages over the direct mutation detection by PCR, including the detection of ADO, chromosomal monosomy and recombination, to ensure the accuracy of clinical diagnosis.…”
Section: Discussionmentioning
confidence: 76%
“…The European Society of Human Reproduction and Embryology (ESHRE) PGD consortium reported that the misdiagnosis rate of the PCR-based method is 0.10% (13/12,790) (De Rycke et al 2017). Several polymorphic markers [short tandem repeats (STRs) or single-nucleotide polymorphisms (SNPs)] located upstream and downstream of the pathogenic genes associated with mutation sites have been used for linkage analysis to establish haplotypes for identifying ADO and to avoid misdiagnosis in PGD (Qubbaj et al 2011;Renwick et al 2006Renwick et al , 2010Chen et al 2016Chen et al , 2017. However, linkage analysis is not feasible for patients without affected relatives.…”
Section: Introductionmentioning
confidence: 99%
“…The protocol for nested PCR was described in our previous study . The total volume of the external amplification reaction was 50 μL, including the following: 5 μL of cell lysis template fluid, 4.5 μL of 10× PCR buffer, 1.5 μL of 50 mmol/L MgCl 2 , 1 UL of 10 mmol/L deoxy‐ribonucleoside triphosphate (dNTP), 0.5 μL of β‐globin amplified primers (at a concentration of 10 mmol/L) and 0.5 U of Taq enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure used for hybridization to amino‐modified oligonucleotides for β‐thalassemia, color detection and analysis of the common mutations in Hemoglobin beta locus was previously described …”
Section: Methodsmentioning
confidence: 99%
“…With the advent of next-generation sequencing (NGS) techniques, an opportunity arises to perform cost�efficient genetic testing by sequencing in different clinical scenarios, which may contribute to definitive improvements in the genetic assessment of embryos prior to transfer to the uterus (19). NGS-based methods, including Mutated Allele Revealed by Sequencing with Aneuploidy and Linkage Analyses and haplotyping analysis, have been successfully applied in SGDs and chromosomal copy number assessment (7,18,20,21).…”
Section: Introductionmentioning
confidence: 99%